The Great Teacher: The Indonesian Adolescent Student Voice - Suyatno, Suyatno; Wantini, Wantini; Prastowo, Andi; Nuryana, Zalik; Firdausi, Dzihan Khilmi Ayu; Samaalee, Abdunrorma (Frontiers in Education, 2022)
The consensus on professional teachers is known to be mostly determined by external parties, especially the government. This prompts professionalism to be considered as an indicator for the need of a great performance in educational sector. However, this consensus method of assessment is of a great disadvantage, because it negates the scope of professionalism. This study aims to use students’ perspectives in conceptualizing the characteristics of professional teachers. Fifteen students were selected as subjects from secondary schools in Yogyakarta city, Indonesia. Two interviews were conducted via electronic media (email and zoom), in order to share their experiences about the characteristics of professional teachers in schools. Also, an interpretive phenomenological analysis was used to analyze the data, in order to understand the participants’ point of view. The results showed that interpersonal relationships, pleasant personalities, and teaching skills, represented the main characteristics of great teachers, according to the students perspectives. These results recommended the importance of emphasizing teacher-student interpersonal relationships, in order to achieve sustainable professional programs.